Basin scale distribution of organic matter in marine fine-grained sedimentary rocks: Insight from sequence stratigraphy and multi-proxies analysis in the Montney and Doig Formations. (May 2017) - Crombez, Vincent; Baudin, François; Rohais, Sébastien; Riquier, Laurent; Euzen, Tristan; Pauthier, Stanislas; Ducros, Mathieu; Caron, Benoit; Vaisblat, Noga
Abstract: The occurrence of hydrocarbons in self-sourced reservoirs strongly depends on the concentration and maturity of organic matter in sediments. Therefore, understanding the distribution of organic heterogeneity at the time of deposition is key to reduce the risk in exploration and development of unconventional resources. This study focuses on the Lower and Middle Triassic Montney and Doig Formations (Alberta and British Columbia). Samples from outcrops, cores and cuttings were analyzed for organic content with a Rock-Eval VI and for major and trace element concentration using ICP-MS and ICP-AES techniques. The interpretation of the analysis results in relation with the stratigraphic architecture provides a mean to better understand the distribution of the organic heterogeneities and the variations of primary productivity, sedimentation rates and anoxia that control the development of source rocks. The key findings of this analysis are: - The basin-scale distribution of the organic matter suggests that the two major source-rock intervals of the Lower and Middle Triassic correspond to the sequence 3 (Spathian Montney unit) and to the transgressive systems tract of sequence 4 (Doig phosphate zone). - The dominant controls on organic matter accumulations vary through time. The Montney source-rock interval is interpreted to be associated with a major basin restriction triggering anoxia during a second-order falling stage of relative sea level. The organic accumulation of the Doig phosphate zone is interpreted as being controlled by a sharp decrease of the sedimentation rate, combined with an increase of the primary productivity. - The spatial and temporal variations of anoxia, primary productivity and dilution reflect the geodynamic evolution of the basin that ultimately controls the basin physiography as well as the sources of nutrient and sediments. Highlights: The Montney and Doig Formations mainly present amorphous organic matter. Rock-Eval data integration in stratigraphic framework shows two organic rich layers. Ni and Cu variations suggest an increased primary productivity in the Doig Phosphate. Redox proxies suggest anoxic intervals in the Upper Montney and the Doig Phosphate.